An investigation on foreign exchange exposure in Malaysia listed companies - Piriya, Selvaraju (2014)
In the light of globalization and internationalization of world markets, foreign exchange risk has become one of the most difficult and persistent problems with which financial executives must cope. This risk cannot be avoided, but can be managed by hedging in currency forwards and options. The need and approach for managing it depends on the size of exposure and fluctuations in exchange rate. Malaysia has its own status in the international markets. This study construct an analysis about foreign exchange exposure Malaysia companies were listed on Kuala Lumpur Stock Exchange during period January 2000 to December 2010. This study extent the prior researches by investigating the effects of major determinants toward the foreign exchange exposure. This study reveals that company efficiency, size, asset tangibility and growth opportunity do affect the foreign exchange exposure in Malaysia companies in general. However, the result comes up differently when those companies classified into their industry sectors. For Industry Product sector, this study documents the evidence that financial leverage, efficiency, profitability and size of the companies are significantly influence the foreign exchange exposure